Hydro-plastic response of beams and stiffened panels subjected to extreme water slamming at small impact angles, part II: Numerical verification and analysis. (May 2019) - Yu, Zhaolong; Amdahl, Jørgen; Greco, Marilena; Xu, Huili
Abstract: An analytical model has been proposed for the response of beams and stiffened panels subjected to extreme flat or nearly flat water impacts in Part I of the two-part companion paper. The model aims to capture the significant hydro-plastic coupling between large plastic structural deformations and the hydrodynamic pressure. Governing non-dimensional parameters for the hydro-plastic slamming phenomenon were identified and discussed. This Part II paper verifies the analytical model proposed in Part I by comparison with the hydro-plastic slamming response of beams and stiffened panels using multi-material Arbitrary Lagrangian Eulerian (ALE) methods in LS-DYNA. Numerical modelling and settings with the ALE simulations are firstly validated by comparison against drop-test experiments of a rigid wedge and of an elastic plate. Then, water entry simulations of flat plates and stiffened panels are carried out, where structural deformations go into the plastic regime. The simulated scenarios cover different plate thicknesses/cross sectional dimensions of stiffened panels, and various initial water-entry velocities. The analytical model is discussed with respect to the fluid flow, structural deflections, the pressure history and the impulse. Validity of assumptions of the analytical model is also discussed. Potential applications and limitations are indicated. The proposed design curves are well suited to be utilized in rules and standards for designing against extreme water slamming. Highlights: The proposed hydro-plastic slamming model is verified of good accuracy by comparison with ALE simulations. The travelling hinge response is well observed from ALE simulations results. The design diagrams against extreme water slamming in ALS conditions are recommended. The model is discussed with respect to elastic effects, impact velocities and the hydro-structure coupling.